The effect of sacral nerve stimulation on distal colonic motility in patients with faecal incontinence. Issue 7 (27th March 2013) - Patton, V.; Wiklendt, L.; Arkwright, J. W.; Lubowski, D. Z.; Dinning, P. G.
<x xml:space="preserve">Abstract</x> Background Sacral nerve stimulation (SNS) is an effective treatment for neurogenic faecal incontinence (FI). However, the clinical improvement that patients experience cannot be explained adequately by changes in anorectal function. The aim of this study was to examine the effect of SNS on colonic propagating sequences (PSs) in patients with FI in whom urgency and incontinence was the predominant symptom. Methods In patients with FI a high‐resolution fibre‐optic manometry catheter, containing 90 sensors spaced at 1‐cm intervals, was positioned colonoscopically and clipped to the caecum. A unipolar or quadripolar tined electrode was implanted into the S3 sacral nerve foramen. Colonic manometry was evaluated in a double‐blind randomized crossover trial, using true suprasensory stimulation or sham stimulation. Each stimulation period, lasting 2 h, was preceded by a 2‐h basal manometric recording. Results All 11 patients studied showed a colonic response to SNS. In ten patients there was a significant increase in the frequency of retrograde PSs throughout the colon during true stimulation compared with sham stimulation (P = 0·014). In one outlier, with baseline retrograde PS frequency nine times that of the nearest patient, a reduction in retrograde PS frequency was recorded. Compared with sham stimulation, SNS had no effect on the frequency of antegrade PSs or high‐amplitude PSs. Conclusion SNS modulates colonic motility in patients with faecal urge incontinence. These data suggest that SNS may improve continence and urgency through alteration of colonic motility, particularly by increasing retrograde PSs in the left colon.